Sustainability performance of Esfahan Steel Company using analytical hierarchy process - Yazdi, Shadi Fekri (2014)
Sustainable development has become an important matter for the steel industry globally, due to the negative impacts of this industrial section on the environment. The main challenge for developing sustainability in steel companies appears to be in implementing sustainability concepts at a company level. Such implementation requires a comprehensive understanding of the company’s current sustainability state, precise specification of sustainability targets, and the determination of the rate and direction of necessary improvement. Esfahan Steel Company (ESCO), one of the biggest Iranian steel makers, faces similar challenge for its transition towards sustainability. Evaluation of its current sustainability performance is the first step to overcome the challenge. Considering a similar sustainable company as a benchmark and comparison of sustainability of both companies is essential for determining the sustainability targets and their specification. The objective of this study is therefore to develop a framework for sustainability assessment of steel industry with the ESCO as the case study including measurement and evaluation of its sustainability performance in comparison with a benchmark. Assessment of sustainability performance using relevant indicators and benchmarking is established as a proper method to monitor companies’ sustainability status. In this thesis, we have presented our approach to measure sustainability performance of the case study company (ESCO) and compared it to a benchmark company which is ranked as one of the highest sustainable steel company in the world. Having defined the benchmark, proper quantifiable sustainability indicators are identified in three categories; economic, environmental and social. The relative preference of the indicators and criteria are determined via a basic AHP approach with pair-wise comparison considering the opinion of the target company's experts. Consistent comparison matrices are further applied for aggregating individual judgments and calculating sustainability performance sub-indices. Finally these subindices are combined to produce composite sustainable performance index for either of the companies to compare. Comparing the target company and the benchmark, in all the sustainability subindices -economic, environmental and social- the performance of the benchmark is higher than the case study; the overall sustainability performance of the benchmark is 1.6 times higher. In addition, comparing the priority weight of the three criteria, the economic criterion plays the most significant role in the sustainability performance of the company, while social plays the lesser significant role after the environmental criterion. The analysis on the relationship between criteria preference and experts’ demographics shows that environment is the most important criterion for sustainability development according to the opinion of experts with Metallurgical background. Regarding the consistency of the experts’ opinion and their demographics, the least percentage of inconsistency in all comparison matrices belongs to the experts aged above 50 and those with more than 30 years work experience. Based on the results, it is concluded that the proposed method can provide a framework for assessing sustainability performance of a steel company. It can pinpoint the area in which the company has deficiency in comparison with a benchmark to be focused on for more improvement. This will facilitate decision making process in prioritizing the resources of the company toward sustainability development. In our study case, investment in environmental facilities and injury cases are the two indicators with the highest priority to invest in to increase the sustainability performance.